(untitled) (Intent Research Scientific Journal, 2024)
This study examines the influence of gender on use of AI generated photographs, and how they create illusion, delusion and make-belief in the mind of the people. The idea behind this study is because of the proliferation of AI-generated images that have overtaken the social media space. The research method adopted for the study is the qualitative research method, leveraging on extensive review of existing literature, documents and articles from reputable journals. The relationship between AI and the digital space is complex and multi-faceted. AI is used to create new digital spaces and experiences, and can also be used to improve existing ones. However, AI is raising questions about privacy, bias, control, and even the nature of personhood. These are important issues that will need to be addressed as AI technology continues to develop. AI generated photographs are a bit of both-they can be both illusion and delusion, depending on how you look at them.